Effectiveness of Balance Exercise in Reducing Fall Risk Among the Elderly - Melly Anisa Putri; Ahmad Nurwanto; Fauziyah Rezkyati (Journal of Advances in Medicine and Pharmaceutical Sciences, 2025)
As individuals enter old age, they typically experience a decline in physical condition, characterized by reduced muscle strength that subsequently impairs bodily movement and functionality. These age-related physical changes often result in mobility impairments, limiting the elderly’s ability to maintain postural stability necessary for performing daily activities, and thereby increasing the risk of falls. Balance disorders are among the primary factors contributing to the elderly’s vulnerability to physical injuries from falls. This study, presented in the form of a literature review, aims to explore strategies for enhancing postural stability as a means to mitigate fall risk among older adults. Employing a scoping review methodology, this research investigates the effectiveness of balance exercise interventions in fall prevention. The literature search was conducted systematically following the PRISMA 2020 Flow Diagram guidelines and utilized three primary databases: PubMed, ScienceDirect, and SAGE Journals. The findings indicate that several exercise-based interventions, such as the Balance-Enhancing Exercise Program (BEEP), Walking Meditation, and Multi-system Physical Exercise (MPE) are effective in reducing the likelihood of falls in the elderly. It is concluded that fall risk is a significant concern among older individuals; however, this risk can be managed, particularly in those who engage in regular physical training and possess sound mental health. Among the evaluated interventions, the Self-Administered Balance-Enhancing Exercise Program (BEEP) appears to be the most effective in minimizing fall risk in elderly populations.